Fretting fatigue characteristics of Ti-6Al-4V alloy with a gradient nanostructured surface layer induced by ultrasonic surface rolling process - Liu, Chengsong; Liu, Daoxin; Zhang, Xiaohua; Ao, Ni; Xu, Xingchen; Liu, Dan; Yang, Jing (International journal of fatigue, 2019)
[Display omitted] •FF strength is effectively improved by USRP with a GNS surface layer.•Compressive residual stress yields more contribution than GNS in raising FF strength.•FF cracks of USRP sample yield a serrated path due to compressive residual stress.•Mechanical surface polishing treatment reduces the FF property. A gradient nanostructured (GNS) surface layer is synthesized on the surface of a Ti-6Al-4V alloy by means of the ultrasonic surface rolling process (USRP). The mean grain sizes on the topmost surface and at depth of 10 μm from the treated surface are approximately 45.8 and 87.5 nm, respectively. Fretting fatigue (FF) testing shows a 113.6% improvement in the fatigue strength after USRP as compared with the untreated condition. The mechanism through which the USRP improves the FF properties can be attributed to the comprehensive effect of the compressive residual stress, GNS surface layer, surface work hardening, and surface roughening. Among these, the compressive residual stress is the main factor in determining the FF behavior, due to the beneficial effect of compressive residual stress on the suppression of FF crack initiation and premature growth.